ANTISIPASI ERA KEPEMIMPINAN KEWIRAUSAHAAN KEPALA SEKOLAH DAN IMPLIKASINYA BAGI PEMBEKALAN ALUMNUS PADA PRODI PENDIDIKAN AKUNTANSI - Budi Sutrisno (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2017)
Entrepreneurial Leadership Headmaster that essentially sees leadership and entrepreneurial leaders on performance, so that its direction is more emphasis on best practices, it has become the issue of secondary education in this period. Consequently, by being led by the Headmaster who has a requirement with his strategic role, accelerates the achievement of graduates besides having competence in his field, has also entrenched entrepreneurial spirit. In practice, this model requires the support and togetherness of all academicians, especially teachers. As an anticipation, for universities, especially LPTKs that supply the needs of teachers, these educational issues become a signal for internal review to review the reliability of more relevant and flexible strategies to find provisions for its alumni. The review will cover several aspects, namely: 1) Leaders and Lecture aspects, 2) Education Laboratory aspects and Accounting, and 3) Aspects of the process of formation and briefing the competence of the graduates. These three aspects essentially refers to the formation of LPTK graduate who later can partner with the Headmaster in realizing the ideals of the school. The accuracy of finding a diagnosis on the aspects that need improvement, accompanied by more innovative strategy determination, and implementation that supported by the entire academic community, will at least be able to provide fresh air for the realization of the vision, mission, and objectives are declared.